University physics with modern physics - Bauer, W. (Wolfgang) 1959- (McGraw-Hill, 2014)
Mechanics of point particles; Extended objects, matter, and circular motion; Oscillations and waves; Thermal physics; Electricity; Magnetism; Optics; Relativity and quantum physics.